2018
DOI: 10.3390/su10061786
|View full text |Cite
|
Sign up to set email alerts
|

Social Sciences, Art and Physical Activity in Leisure Environments. An Inter-Disciplinary Project for Teacher Training

Abstract: Factors such as social change and increasing urbanization processes in the early years of the 21st century have caused a reduction in the amount of time that children devote to leisure activities in the open-air, resulting in more sedentary lifestyles than children in previous decades. An education in healthy habits from early ages to increase children's physical and mental well-being together with their level of cultural knowledge contributes to the acquisition of a Leisure Culture that allows children to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(48 reference statements)
1
2
0
2
Order By: Relevance
“…Studies have shown that experimenting with ways to improve student formative activity through curricular diversification creates favorable conditions for training attitudes and extending professional skills to future physicists [33,34]. Examination of the field literature shows that there are a number of studies [35,36,37,38] carried out in this country and abroad that show parallels with the findings of this study. In this way, the study revealed the positive impact of different specific activities of physical education on the psychological and mental levels of students [39], on the social integration and relationships level of students [40,41,42] and on the physical fitness [19,43,44,45].…”
Section: Discussionsupporting
confidence: 79%
“…Studies have shown that experimenting with ways to improve student formative activity through curricular diversification creates favorable conditions for training attitudes and extending professional skills to future physicists [33,34]. Examination of the field literature shows that there are a number of studies [35,36,37,38] carried out in this country and abroad that show parallels with the findings of this study. In this way, the study revealed the positive impact of different specific activities of physical education on the psychological and mental levels of students [39], on the social integration and relationships level of students [40,41,42] and on the physical fitness [19,43,44,45].…”
Section: Discussionsupporting
confidence: 79%
“…En este tipo de actividades no solo se consigue un desarrollo competencial en una realidad más cercana al alumnado, sino que además origina una mejora en la motivación y el interés por el aprendizaje. Así se desprende de los resultados que recogemos en esta investigación, en la que el alumnado de secundaria valora muy positivamente este tipo de actividades y que están de acuerdo con otros estudios similares realizados bien con alumnado de secundaria o bien con alumnado universitario (Alcántara y Medina, 2019;Cheng, Hwang y Chen, 2019;Martín, 2016;Montero y Jerez, 2019;San Pedro et al, 2018), y que constatan que este tipo de proyectos permite el desarrollo de múltiples competencias así como su carácter interdisciplinar posibilita el acercamiento y aprendizaje de diversas disciplinas. Sólo un pequeño porcentaje, un 12%, no encuentra la actividad motivadora o con el suficiente interés por aprender.…”
Section: Discussionunclassified
“…Although the majority of studies carried out on the use of didactic itineraries as a resource for learning coincide in affirming that the use of smartphones, augmented reality, geolocation, and social networks help to improve interest, motivation, and learning among students [35,46,[49][50][51][52][53]; on this occasion, we cannot affirm the same, since a very discreet result was obtained. One of the reasons that explains this poor result, compared to a notable result obtained on a previous occasion with a very similar approach [35], is the fact that, on the day of the activity, despite having been postponed and rescheduled twice for the same reason, the rain made its appearance, with this being, at some times of the day, quite intense and annoying.…”
Section: Discussionmentioning
confidence: 95%